The Asymmetric Precipitation Evolution in Weak Landfalling Tropical Cyclone Rumbia (2018) Over East China - Tang, Lichun; Wang, Yuqing; Yu, Zifeng; Wang, Lan (Frontiers in Earth Science, 2021)
The rainfall in landfalling TC is not always correlated with the storm intensity. Some weak landfalling TCs could bring extremely heavy rainfall during and after landfall. Such extreme events are very challenging to operational forecasts and often lead to disasters in the affected regions. Tropical storm Rumbia (2018) made its landfall in Shanghai with weak intensity but led to long-lasting and increasing rainfall to East China. The asymmetric rainfall evolution of Rumbia during and after its landfall was diagnosed based on the fifth generation European Centre for Medium-Range Weather Forecasting (ECMWF) reanalysis (ERA5) data, the tropical cyclone (TC) best-track data, and rainfall observations from China Meteorological Administration (CMA). Results showed that Rumbia was embedded in an environment with a deep-layer (300–850 hPa) southwesterly vertical wind shear (VWS). The maximum rainfall mostly occurred downshear-left in its inner-core region and downshear-right in the outer-core region. The translation of Rumbia also contributed to the rainfall distribution to some extent, especially prior to and just after its landfall. The strong southwesterly-southeasterly summer monsoon flow transported water vapor from the tropical ocean and the East China Sea to the TC core region, providing moisture and convective instability conditions in the mid-lower troposphere for the sustained rainfall even after Rumbia moved well inland. The results also showed that the low-level convective instability and the deep-layer environmental VWS played an important role in deepening the inflow boundary layer and the redevelopment of the secondary circulation, thus contributing to the heavy rainfall in the northeast quadrant of Rumbia after its landfall. However, further in-depth studies are recommended in regard of the rainfall evolution in the weak TCs. This study further calls for a continuous understanding of the involved physical processes/mechanisms that are responsible for the extreme rainfall induced by landfalling TCs, which can help improve the rainfall forecast skills and support damage mitigation in the future.